A new species of Colobothea Lepeletier & Audinet-Serville, 1825 (Coleoptera: Cerambycidae: Lamiinae) from Ecuador - Souza, Diego De Santana (Zootaxa, 2016)
Colobotheini is a tribe of Lamiinae (Cerambycidae) which includes 189 species classified into 12 genera (Monné, 2016). This tribe is characterized by a trapezoidal frons, contiguous antennal tubercles, prothorax without lateral spines, elytra elongate with lateral carina, metatarsomere I elongate and tarsal claws divaricate (Galileo & Martins, 2006). Colobothea Lepeletier & Audinet-Serville, 1825 is the largest genus of Colobotheini, with 119 valid species distributed from Mexico to Southern South America, except Chile and latitudes below 35°S.